Urinary Estrogen Metabolites and Self-Reported Infertility in Women Infected with Schistosoma haematobium - Julio Santos (2014)
Background: Schistosomiasis is a neglected tropical disease, endemic in 76 countries, that afflicts more than 240 million people. The impact of schistosomiasis on infertility may be underestimated according to recent literature. Extracts of Schistosoma haematobium include estrogen-like metabolites termed catechol-estrogens that down regulate estrogen receptors alpha and beta in estrogen responsive cells. In addition, schistosome derived catechol-estrogens induce genotoxicity that result in estrogen-DNA adducts. These catechol estrogens and the catechol-estrogen-DNA adducts can be isolated from sera of people infected with S. haematobium. The aim of this study was to study infertility in females infected with S. haematobium and its association with the presence of schistosome-derived catechol-estrogens. Methodology/Principal Findings: A cross-sectional study was undertaken of female residents of a region in Bengo province, Angola, endemic for schistosomiasis haematobia. Ninety-three women and girls, aged from two (parents interviewed) to 94 years were interviewed on present and previous urinary, urogenital and gynecological symptoms and complaints. Urine was collected from the participants for egg-based parasitological assessment of schistosome infection, and for liquid chromatography diode array detection electron spray ionization mass spectrometry (LC/UV-DAD/ESI-MSn) to investigate estrogen metabolites in the urine. Novel estrogen-like metabolites, potentially of schistosome origin, were detected in the urine of participants who were positive for eggs of S. haematobium, but not detected in urines negative for S. haematobium eggs. The catechol-estrogens/DNA adducts were significantly associated with schistosomiasis (OR 3.35; 95% CI 2.32-4.84; P <= 0.001). In addition, presence of these metabolites was positively associated with infertility (OR 4.33; 95% CI 1.13-16.70; P <= 0.05). Conclusions/Significance: Estrogen metabolites occur widely in diverse metabolic pathways. In view of the statistically significant association between catechol-estrogens/DNA adducts and self-reported infertility, we propose that an estrogen-DNA adduct mediated pathway in S. haematobium-induced ovarian hormonal deregulation could be involved. In addition, the catechol-estrogens/DNA adducts described here represent potential biomarkers for schistosomiasis haematobia.